Codon Usage is Influenced by Compositional Constraints in Genes Associated with Dementia - Alqahtani, Taha; Khandia, Rekha; Puranik, Nidhi; Alqahtani, Ali M.; Alghazwani, Yahia; Alshehri, Saad Ali; Chidambaram, Kumarappan; Kamal, Mohammad Amjad (Frontiers in Genetics, 2022)
Dementia is a clinical syndrome characterized by progressive cognitive decline, and the symptoms could be gradual, persistent, and progressive. In the present study, we investigated 47 genes that have been linked to dementia. Compositional, selectional, and mutational forces were seen to be involved. Nucleotide components influenced codon usage bias, which is affected by nucleotide composition A and GC at all three codon positions. The influence of these two compositional constraints on CUB was positive for nucleotide A and negative for GC. Nucleotide A also experienced the highest mutational force, and GC ending codons were preferred over AT ending codons. A high bias towards GC-ending codons enhances the gene expression level, evidenced by the positive association between CAI and GC-ending codons. Unusual behavior of TTG codon showing an inverse relationship with GC ending codon and negative influence of gene expression, behavior contrary to all other GC ending codons, shows operative selectional force. Furthermore, parity analysis, higher translational selection value, preference of GC ending codons over AT ending codons, and association of gene length with gene expression refer to the dominant role of selection pressure with compositional constraint and mutational force also in shaping codon usage.